Ilham Aliyev - Historical traditions of statehood in Azerbaijan and promotion of multiculturalism - Oqlu, Mammadov Mehmanali Akbar; Habib, Alizade (Technium Social Sciences Journal, 2022)
The Republic of Azerbaijan has ancient traditions of statehood. Looking at these traditions, which have passed the test of history, it becomes clear that Azerbaijan has historically been a multinational state. In this sense, it is very important to pursue the policy of multiculturalism, characteristic of multinational states, in the right direction. The article tells about the policy of multiculturalism pursued by President Ilham Aliyev in the multinational Republic of Azerbaijan and its results.